تعطيل العمل بالدستور بين جدلية الضرورة و الخيار في الأنظمة الدستورية المقارنة - تريعة, نوارة; والي, عبد اللطيف (University of Eloued جامعة الوادي, 2020)
تعطيل العمل بالدستور هو توقيف العمل بأحكامه أو تعليق قواعده لمدة قد تطول أو تقصر، و هو ينقسم من حيث نطاق مشروعيته إلى التعطيل الدستوري المشروع أو الرسمي و التعطيل الدستوري الغير مشروع، و ينقسم من حيث نطاق موضوعه إلى التعطيل الدستوري الجزئي و الكلي، و الهدف من هذه الدراسة هو إبراز الدور الذي يلعبه هذا الإجراء في تركيز السلطة و ما ينجر عنه من اعتداء على الحقوق و الحريات المضمونة بموجب نصوص الدستور في ظل ضوابط قانونية و واقعية متباينة، من خلال وصف و تحليل نماذج من دول مختلفة و مقارنتها. Disruption of work The constitution is the suspension of the implementation of its provisions or the suspension of its rules for a period that may be longer or shorter, and it is divided in terms of the scope of its legitimacy to the legal, official and illegal suspension, and is divided in terms of the scope of its subject matter into partial and total, The aim of this study is to highlight the role that this procedure plays in concentrating power and the resulting assault on the rights and freedoms guaranteed by the provisions of the constitution in light of different legal and realistic controls, by describing and analyzing models from different countries and Compare it.
مجلد11، عدد3
Keywords: تعطيل الدستور؛ رئيس الدولة؛ حالة الضرورة؛ الانقلاب العسكري؛ الواقع الدستوري; Disrupting the constitution; the president of state; the state of necessity; the military coup; the constitutional reality